Colon cancer in malrotated gut: A case report - Gupta, Arnab; Sahu, Subrata Kumar; Bhattacharya, Samir; Haldar, Sudip (Indian Journal of Case Reports, 2021)
Malrotation of the gut is a rare congenital anomaly that mostly presents in the 1st month of life. Very rarely, it is found during adulthood either as an asymptomatic incidental finding or at autopsy. Presenting in adulthood with colon cancers is extremely rare. Here, we present the case of a middle-aged male patient with unexplained anemia which on investigation was found to have adenocarcinoma at the hepatic flexure of the colon. The staging computed tomography scan of the abdomen showed the growth at the hepatic flexure with malrotation of the gut. During the laparoscopic assessment, the cecum and ascending colon were found on the left side, and hence, a formal midline incision was made. Cecum was found on the left of the midline along with Ladd’s band. Extended right hemicolectomy was performed, dividing the Ladd’s band, taking care of the anomalous position of superior mesenteric vessels. The post-operative period was uneventful. Histopathological examination revealed this to be well-differentiated adenocarcinoma (pT3N1b). He thereafter received adjuvant chemotherapy and remains well after 5 years of follow-up. Presentation of malrotation of the gut in adulthood is seen in only 10–15% of cases as an incidental finding or at autopsy. Cancers in the colon in these patients are extremely rare. The treatment for colon cancer remains the same although one has to be careful about the vascular anomaly during the resection.